Gestión logística internacional y los vehículos autónomos (2022)
Autonomous vehicles are a disruption of the automotive industry that has gained popularity in international logistics management and that can contribute to the development of said operations. That is why, in the current monographic work, the incorporation of autonomous transport vehicles in international logistics management is studied; for this, three chapters were developed, the first describes the general aspects of autonomous vehicles, their origin, applications, the components that guarantee their operation and the regulations that govern them; This information is of special relevance to have a first approach with this technology and the needs that it can satisfy. The second chapter presents the autonomous transport vehicles that have been incorporated into international logistics management processes, the companies that are developing innovations in this field, and the tests and prototypes that have been carried out at a global level are shown. The last chapter points out the economic benefits of using autonomous vehicles in international logistics management processes, compared to conventional vehicles; similarly, its competitive advantages in terms of costs, delivery times and customer satisfaction are highlighted; and as a counterpart, the disadvantages associated with its adoption, the limitations of its massive deployment and the barriers that it currently has are mentioned.